The Control of Diabetes Mellitus in Coastal Communities in Surabaya Region - Yuliastuti, Christina; Arini, Diyah; Sari, Mufhida Praningtyas Enggar (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Prevention of complications of diabetes mellitus requires good control of diabetes mellitus. Based on Basic Health Research Data of the Ministry of Health, in the end of 2013, the number of diabetic patients in Indonesia had reached 9.1 million and this number continues to grow which in 2030, the number is predicted to reach 21.3 million. This study aimed to identify the paramaters of diabetes mellitus control. This descriptive study involved 30 diabetic patients in coastal communities of Surabaya who were randomly selected. Data collection was undertaken using an observation sheet and diabetes control measurement tools. The data were analyzed descriptively. The results showed that diabetes control were mostly poor based from the indicator of fasting blood glucose level (181.77±68.728) and two hours postprandial blood glucose level (277.07±111.884). Meanwhile, total cholesterol (196.43±60.640), blood pressure (systolic 125±16.969 and diastolic 78±8.469), and Body Mass Index (23,257±3,231) were good. Education on Self Care Management will support the control of diabetes mellitus.